Variabilidade da coordenação interarticular entre cotovelo e punho durante o alcance em indivíduos hemiparéticos crônicos - Trevisan, Claudia (2021)
The loss or functional alteration of the upper limb (MS) is one of the most common reports of post-stroke individuals, who have limitations in tasks of daily living, especially those that involve reaching. Among the changes that limit the functionality of the upper limb are changes in strength, proprioceptives and muscle synergies, which reflect on the ability of interarticular coordination and variability of the movement. Objective: to evaluate the variability of interarticular coordination of the elbow and wrist in chronic hemiparetic individuals in reaching movement. Methods: This is a subanalysis that evaluated eleven chronic hemiparetic individuals and 11 healthy individuals matched for age and sex. During simulation of the drinking activity at a self-selected speed, performed with an acrylic glass with water, divided into the reach of the glass (phase 1), take the glass to the mouth (phase 2) and return the glass to the table (phase 3), data were obtained regarding changes in intra-limb coordination variability (elbow and wrist) in the sagittal plane, using the vector coding technique in addition to the construction of an angle-angle graph (cyclogram). The spatiotemporal variables complemented the analyzes. The spatiotemporal variables analyzed were as follows: duration of the task (seconds and percentage), peak speed (mm / s), time to peak speed (%). Results: differences in the quality of the joint coordination pattern and variability of intra-limb joint coordination between the hemiparetic and control groups were observed in the phases of reaching the cup (phase 1), taking the cup to the mouth (phase 2) and return of the glass to the table (phase 3). In the spatiotemporal variables, differences between groups were observed in the variables duration of movement (s) (HG = 2.42 s (0.80), CG = 1.39 s (0.27)), peak velocity (HG= 285.00 s (63.25), CG = 385.93 (63.91)), peak speed time (%) (HG = 29.51 s (11.39), CG = 41.95 s (10.10) in phase 1, duration (%) (HG = 24.15 (3.55), CG = 29.46 (4.39)) peak velocity (HG = 425.21 (215.13) CH = 489.96 (122.28)) and peak velocity time (%) (HG = 46.48 (23.97), CG = 27.33 (8.24)) in phase 2, and duration of movement (s) (HG = 2.96 (1.03), CG = 1.96 (0.38)) and time of peak velocity (%) (HG = 26.04 (9.86) CG = 40.25 (7.51)) in phase 3. Conclusion: Chronic hemiparetic individuals show changes in variability and interjoint coordination during reaching movements, making movement slower during the functional task of drinking.